THE EFFECT OF DISTRIBUTION FUNDS OF ZAKAT INFAQ SHADAQAH, SOCIAL ASSISTANCE EXPENDITURE, AND SUBSIDY EXPENDITURE ON POVERTY IN INDONESIA - Mulazid, Ade Sofyan; Mufliha, Nurul Mudhiatil (Islamic Economics Program, Faculty of Islamic Economics and Business, 2019)
This study aims to analyze the effect of the distribution funds of Zakat Infaq Shadaqah (ZIS), social assistance expenditure and subsidy expenditure on poverty in Indonesia 2013-2017 period. The sample from this study consisted of ZIS data obtained at the National Alms Agency (known as BAZNAS). Then social assistance expenditure and subsidy expenditure and the latest poverty data obtained at the Central Statistics Agency (BPS). In this research, the method used multiple linear regression analysis by testing classical assumptions. The results of this study are according to the results of the F test that the three independent variables (ZIS, social assistance expenditure and subsidy expenditure) have a simultaneous effect on the dependent variable (poverty) by having a significance value of 0,000, which means less than 0.05.Furthermore, it is supported by the results of the T-test that the three independent variables partially have a significant effect on the dependent variable, with a significance value in the ZIS variable was 0,000. Then, social assistance expenditure was 0.025. The last, subsidy expenditure was 0,000. It means lower than 0.05